CCL19‐positive lymph node stromal cells govern the onset of inflammatory arthritis via tropomyosin receptor kinase - Schälter, Fabian; Azizov, Vugar; Frech, Michael; Dürholz, Kerstin; Schmid, Eva; Hendel, Anna; Sarfati, Ilann; Maeda, Yuichi; Sokolova, Maria; Miyagawa, Ippei; Focke, Kristin; Sarter-Zaiss, Kerstin; et al. (Arthritis and Rheumatology, 2024)
Objectives To assess the role of CCL19+ lymph node stromal cells of the joint draining popliteal lymph node (pLN) for the development of arthritis. Methods CCL19+ lymph node stromal cells were spatiotemporally depleted for 5 days in the pLN before the onset of collagen-induced arthritis (CIA) using Ccl19-Cre x iDTR mice. In addition, therapeutic treatment with recombinant CCL19-IgG, locally injected in the footpad, was used to confirm the results. RNA sequencing of lymph node stromal cells combined with T cell co-culture assays using tropomyosin receptor kinase (Trk) family inhibitors together with in vivo local pLN siRNA treatments were used to elucidate the pathway by which CCL19+ lymph node stromal cells initiate the onset of arthritis. Results Spatiotemporal depletion of CCL19+ lymph node stromal cells prevented disease onset in CIA mice. These inhibitory effects could be mimicked by local CCL19-IgG treatment. The mRNA sequencing analyses showed that CCL19+ lymph node stromal cells downregulated the expression of the tropomyosin receptor kinase A (TrkA) just before disease onset. Blocking TrkA in lymph node stromal cells led to increased T cell proliferation in in vitro co-culture assays. Similar effects were observed with the pan-Trk inhibitor Larotrectinib in co-cultures of lymph node stromal cells of rheumatoid arthritis patients and T cells. Finally, local pLN treatment with TrkA inhibitor and TrkA siRNA led to exacerbated arthritis scores. Conclusions CCL19+ lymph node stromal cells are crucially involved in the development of inflammatory arthritis. Therefore, targeting of CCL19+ lymph node stromal cells via TRK kinases could provide a tool to prevent arthriti

The role of joint-draining lymph node stromal cells in inflammatory arthritis - Schälter, Fabian; Azizov, Vugar; Frech, Michael; Dürholz, Kerstin; Sokolova, Maria; Hendel, Anna; Focke, Kristin; Sarter-Zaiss, Kerstin; Van Baarsen, L. G. M.; Krautwald, S.; Schett, Georg; Zaiss, Mario (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27